Economic Colonialism: Korean Wave (Hallyu) Hegemony - Frischa Faradilla Arwinda Mongan; Bertha Beloan; Ni Nyoman Ayu Suryandari; Maria Yessica Halik (Yayasan Rumah Peneleh, 2022)
This study aims to make people aware that the hegemony of the Korean Wave is a form of economic colonization. The Korean wave is a soft power instrument used by South Korea for economic gain, through music (K-pop), drama (K-drama) and film (K-film). This study employed Derrida’s deconstruction as a way of reading the text carefully, playing with and disturbing the stability of the meaning embedded in the text. The findings indicate the benefits derived from the spread of the Korean Wave give rise to the meaning of economic colonization. Almost all countries in the world are under this hegemony by consuming music, drama and film products from South Korea.